Comparative Study of Transmission Line and Cavity Model of Rectangular Microstrip Antenna - Banerjee, P; Bezboruah, T (International Journal of Natural Sciences Research, 2015)
In this paper a comparative study is carried out to estimate the performance of transmission line and cavity models of rectangular microstrip antenna mounted on six dielectric substrate materials with variable substrate heights. An artificial intelligence technique, namely: MATLAB based Adaptive Neuro-Fuzzy Inference System is used to optimize the length and width of the antenna. Random data sets are generated and experimental data are used to carry out the optimization of various antenna parameters to cover almost entire cellular spectrum. With operating frequency of 2.1GHz, we analyze the bandwidth of the antenna of both the models. The simulation results predict that the cavity model of rectangular microstrip antenna perform well over transmission line model with thick substrate while transmission line model is better at low dielectric constant and thin substrate.